The Religious Charismatic Leadership of Sultan Mahmud Badaruddin II (1803-1821) in the Study of Menteng War Poetry - Andaryani, Sutinah; Idi, Abdullah; Wijaya; Noupal, Muhammad (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2024)
This research began with an interest in leadership studies in the implementation of public administration that occurred during the era of Sultan Mahmud Badaruddin II. The aim is to comprehensively explain religious charismatic leadership in the implementation of the power system of the Palembang Darussalam kingdom during the era of Sultan Mahmud Badaruddin II (1803 – 1821) through a study of the Menteng War manuscript, its transliteration along with analysis. The theories used are Leadership, Legitimacy, Bureaucracy, Public Administration, Public Policy, and Public Management. This research, which is located in the city of Palembang, is library research with a qualitative historical method approach. The primary data in this research is the Menteng War Poetry manuscript and several books published during the reign of Sultan Mahmud Badaruddin II. There is also secondary data in the form of journals, articles, and data from interviews using purposive snowball techniques as support for this research. The analysis techniques used by historical methods are Heuristics (source search process), Verification (source criticism), and Interpretation (analysis in data systems). The results of the research obtained are that in the poetry the use of sentences or words that are shouted during the war such as the Gift of Allah Subhani, the Gift of God the Almighty, La illahailla'llah, Allahu Akbar the help of Maliku'l Jabbar, the use of the words martyrdom, heaven, angel, castor oil, hell, devil, charm, Sultan is like a warrior, Palembang people are like eagles, words that show that the Sultan is intelligent, a war strategist, motivating transmits positive energy, very wise, has compassion and forgives (forgives), which is very strong as a value in religious charismatic leadership. Also, various decrees of the Sultan show the existence of public policy, legitimacy, and bureaucracy that had occurred at that time.